Effects of concentrate supplement on camel performance, forage utilization, and energy usage in arid-area rangelands - Ahmed R. Askar; Ahmed R. Saber; Sabbah Allam; Khaled Z. Kewan; Mohammed H. Bakr; Faysal Fayed; Hamedi M. Kandil; Samy Abo Ragab; Basma A. Hussien; Samir S. Abou El Ezz; Mohsen M. Shoukry (BMC Veterinary Research)
Abstract Background In light of climate change, camels, as drought-resistant animal species, have become a crucial component of the pastoralists' economy, ecology, and culture. They exhibit an extraordinary capacity to adapt to harsh environments. Most camels rely on grazing on natural rangelands to meet their daily nutritional requirements. Climate and watering intervals influence the foraging behavior of camels, as well as forage quality and availability. This experiment investigated the effects of adding a concentrate supplement (CS) on camel performance, forage consumption and digestibility, and energy usage in arid-area rangelands during the dry season. Methods Eighteen dry and non-lactating she-dromedary camels, aged 8–10 years and weighing an average of 438 ± 5.7 kg, were employed in the experiment. Camels were randomly selected from a herd of 120 animals, individually marked for identification, and divided into three groups of six. The CS was administered separately before grazing at 0% (control), 50% (low), and 100% (high) of the metabolizable energy requirements for maintenance. The herd grazed daily from 08:00 to 18:00 in an area dominated by Ababasis articulate, a low-quality forage containing more than 70% neutral detergent fiber. Results Adding a high CS level alleviated animal deterioration by reducing weight loss from − 1049 to − 192 g/day and significantly increasing dry and organic matter digestibility. A substantial drop in forage consumption, accompanied by a significant adverse effect on fiber digestibility (P < 0.01), was observed with CS addition. The Global Positioning System results revealed that the high CS addition considerably reduced (P < 0.01) the distance traveled from 25 to 13 km, leading to lower (P < 0.01) walking and grazing activity and higher (P < 0.01) standing and resting time. The results were consistent with energy expenditure data, reflected in a more incredible retained energy for high vs. low or control levels of the concentrate. Conclusions It is recommended that camels be confined and not allowed to graze, or they graze for a shorter period of time during drought seasons when palatable forage is scarce. Supplementary feeding is essential to maintain camels in arid-area rangelands. When CS is utilized, the interdependent effects on forage utilization must be considered. The CS should be used under restriction or replaced partially or completely with high-quality forage during the drought season.